Ovarian cancer risk factor associations by primary anatomic site: The Ovarian Cancer Cohort Consortium - Fortner, RT; Rice, MS; Knutsen, SF; Orlich, MJ; Visvanathan, K; Patel, AV; Gaudet, MM; Tjønneland, A; Kvaskoff, M; Kaaks, R; Trichopolou, A; Pala, V; et al. (American Association for Cancer Research, 2020)
Background: Epithelial ovarian, fallopian tube, and primary peritoneal cancers have shared developmental pathways. Few studies have prospectively examined heterogeneity in risk factor associations across these three anatomic sites. Methods: We identified 3,738 ovarian, 337 peritoneal, and 176 fallopian tube incident cancer cases in 891,731 women from 15 prospective cohorts in the Ovarian Cancer Cohort Consortium. Associations between 18 putative risk factors and risk of ovarian, peritoneal, and fallopian tube cancer, overall and for serous and high-grade serous tumors, were evaluated using competing risks Cox proportional hazards regression. Heterogeneity was assessed by likelihood ratio tests. Results: Most associations did not vary by tumor site (Phet ≥ 0.05). Associations between first pregnancy (Phet = 0.04), tubal ligation (Phet = 0.01), and early-adult (age 18–21 years) body mass index (BMI; Phet = 0.02) and risk differed between ovarian and peritoneal cancers. The association between early-adult BMI and risk further differed between peritoneal and fallopian tube cancer (Phet = 0.03). First pregnancy and tubal ligation were inversely associated with ovarian, but not peritoneal, cancer. Higher early-adult BMI was associated with higher risk of peritoneal, but not ovarian or fallopian tube, cancer. Patterns were generally similar when restricted to serous and high-grade serious cases. Conclusions: Ovarian, fallopian tube, and primary peritoneal cancers appear to have both shared and distinct etiologic pathways, although most risk factors appear to have similar associations by anatomic site. Impact: Further studies on the mechanisms underlying the differences in risk profiles may provide insights regarding the developmental origins of tumors arising in the peritoneal cavity and inform prevention efforts.